DAMPAK LONGSORAN KALDERA TERHADAP TINGKAT SEDIMENTASI DI WADUK BILI-BILI PROVINSI SULAWESI SELATAN - Asrib, Ahmad Rifqi; J Purwanto, Yanuar; S, Sukandi; ,, Erizal (Universitas Jambi, 2011)
ABSTRACTThis research aimed to study impact of caldera landslide at Jeneberang sub watershed to sedimentation rates in the Bili-Bili dam. The research was conducted based on field survey, caldera landslide at upstream and sedimentation rate in the Bili-Bili dam. The Result Showed that Jeneberang sub watershed dominated by steep areas topography is 10.080 ha (26.22%) and the closure of forested land is 12.250 ha (31.87%). Caldera landslide in 2004 caused sediment flow from upstream of Jeneberang watershed was 45,027,954 m3. Sabo dam as a sediment control along the Jeneberang upstream has function effectively. It was seen from the volume flow of sediment that can be controlled up to the year 2008 is 1,915,671 m3. Sedimentation rate before the event of landslide caldera, sediment deposited in Bili-Bili dam cumulatively is 8.376 million m3 (April 2001). Five years after the landslide sediment volume has reached 60.959 million m3 in 2008. Based on Trap efficiency showed that efficiency of Bili-Bili dam was decrease from 90.81% in 1997 to 73.34% in 2005, and then increased in 2007 (92.57%) and in 2008 decrease become 89.79%.